Distinct Psychological Profiles Linking Childhood Adversity and Substance Misuse in High-Risk Young Adults - van Zyl, Tara-Lynne (Journal of family violence, 2023)
Adverse childhood experiences (ACEs) constitute a key determinant in the development of substance misuse. However, the understanding of how ACEs cultivate this risk lacks the specificity needed to inform effective prevention and intervention practices. This issue may be remedied by exploring the distinction between ACEs and their effects on development. The present study investigated whether distinct patterns of adversity are differentially associated with substance misuse along unique profiles of psychological variables, namely anxiety and punishment sensitivity – an internalizing profile – versus reward sensitivity and executive functioning – an externalizing profile. Using a cross-sectional retrospective design, 124 high-risk young adults completed assessments of childhood adversity and psychological functioning. We employed the ACE-IQ to capture extended ACEs such as community and collective violence, as our sample grew up in the post-conflict society of Northern Ireland. Exploratory Factor Analysis revealed three patterns of adversity co-occurrence – Childhood Maltreatment, Household Dysfunction and Community Adversity, all of which independently predicted different types of substance misuse. Childhood Maltreatment was significantly associated with heavy drug use probability; Household Dysfunction was associated with cannabis dependence probability; and Community Adversity was associated with both cannabis dependence and heavy drug use probability. Logistic regressions (all p < .05) showed that heavy drug use probability was predicted by Childhood Maltreatment and anxiety in one model, and by Community Adversity and reduced punishment sensitivity in another, suggesting that different types of ACEs were associated with partially distinct outcomes in this sample. These results support the proposal that different ACE subtypes confer distinct effects, which carries clinical implications for substance misuse prevention and intervention.